Commercial fertilizers and organic additives in orchid micropropagation - Moraes, Milena Cristina; Camolesi, Mara Rubia; Palmieri, Darío Abel; Bertão, Mônica Rosa (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2020)
In vitro cultivation strategies promise conservation and micropropagation of vulnerable or economically exciting plants, especially in Orchidaceae. Numerous reports are available for an extensive contingent of orchids of the most varied genera, and the main issue is related to the behavior of species during the process of germination and growth concerning the nutrients used in the culture media. In Orchidaceae, several evidence support that each species responds differently and specifically according to the biotic and abiotic conditions available for in vitro growth. The main concern is to seek simplified culture media that promote germination and the development of healthy plants on a large scale. This study assessed the behavior of Catasetum fimbriatum and Catasetum macrocarpum in culture media containing commercial fertilizers supplemented with organic additives, compared with traditional media, an economically more viable strategy for micropropagation. Seeds were cultured on traditional nutrient media or with commercial fertilizer and organic additives in different combination. The analysis of plant growth after 120 days in vitro showed that the best treatment in both species was the medium containing commercial foliar fertilizer Peters NPK® 10:30:20 supplemented with potato and banana pulp. Index terms: Tissue culture; Orchidaceae; simplified medium; Catasetum.